Penyuluhan Hukum Hak Atas Tanah di Kawasan Pesisir Desa Wawobungi Kecamatan Lalonggasumeeto Kabupaten Konawe - Hasima, Rahman (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2023)
The need for land is not only felt by people in urban areas, but also people living on small islands. People who live on small islands that are inhabited and have easy access from the local government center have a fairly high population growth rate which results in their need for land is also getting higher while the available land is very limited and has been used to build houses and other buildings, so they are trying to find solutions to meet their needs for land. One solution is to find land in peripheral areas such as coastal areas. The method used in legal counseling activities with lecture and question and answer methods to explore public knowledge of the material provided. The results of the activity showed that legal counseling can increase the knowledge and understanding of the people of Wawobungi Village related to the policy of granting land rights in coastal areas so that it has an impact on increasing understanding and awareness of community law in terms of regulation of land rights in coastal areas and participants are able to understand and know the policy of granting land rights in coastal areas which can be shown by the participation of participants in Participating in legal counseling activities from the beginning to the end of the activity aimed at the questions asked by participants in the question and answer session.